Produção de bio-hidrogênio a partir do efluente da parboilização do arroz - Leite, Tatiane Lotufo (2010)
The growing demand for energy and attempt to replace the energy matrix based on fossil fuels causes exist multiple searches in the search for alternative fuels. Hydrogen gas, which has potential energy 2.5 times larger than any hydrocarbon, and when burned releases only water, being their combustion free greenhouse gas potentializing. Several processes have been used for the production of biohydrogen. Of these processes is based on anaerobic degradation of waste, especially rich in carbohydrates. The parboiling is a process hydrothermal treatment of rice in the husk, which aims to improve the nutritional quality of the product. The rice parboiling generates approximately 4 L of effluent per kilogram of rice. This effluent presents a high content of organic substances and nutrients such as nitrogen and phosphorus, showing significant concentrations of carbohydrates also. The potential of hydrogen production from the effluent of parboiling rice was tested on reactors with anaerobic sludge of UASB heat-treated with sludge acidogenic hydrogen producer. Also studied the need for addition of nutrients to effluent parboiled for hydrogen production. The pH of the experiment was kept 5.5 to avoid growth of arquea metanogenic, that consume hydrogen. The temperature of the reactor was maintained at 20 ± 5 ºC. The experiment was mounted in batch of 48 hours, using sucrose as substrate control. The effluent from parboiled rice presents an average concentration of COD gross 4988.6 mg L-1 and carbohydrate 1030.0 mg L-1. Of the UASB anaerobic sludge heat-treated produced hydrogen with maximum rate of 62, 3 mL. g-1 COD removed, while the slime acidogenic produced 217.5 mL g-1 COD removed. The acidogenic reactor fed with effluent from parboiling presented removing 32.9% COD and 77.8% carbohydrates. Maximum production of hydrogen from the effluent was 9, 61 mL. Hydrogen gas production per gram of SSV in acidogenic reactor fed with sucrose was superior to reactor fed with effluent from parboiling. Reactors with three different gradients of addition of nutrients have been tested, showing that the hydrogen production was not significantly increased with increasing concentration of nutrient solution, indicating that the effluent from parboiling has potential for hydrogen production by anaerobic processes without the need for addition of nutrients tested.